The The Role of Supportive Leadership and eHealth Literacy in Fostering Employee Well-being in SMEs - Evi Kurniasari Purwaningrum; Nuraida Wahyu Sulistyani; Intan Suraya (Universitas Ahmad Dahlan, 2026)
Employee well-being underpins performance, safety, and productivity, yet workplace mental health is often undervalued and stigmatized in Indonesian small and medium-sized enterprises (SMEs). This study tested an integrated model in which supportive leadership relates to employee well-being directly and indirectly via employees’ engagement in mental health, with eHealth literacy examined as a boundary condition. Survey data were collected from 278 SME employees (purposive sampling) and analyzed using structural equation modeling. Engagement in mental health (β = 0.536, p < .001) and supportive leadership (β = 0.289, p < .001) were positively associated with employee well-being (R² = 0.485). eHealth literacy strengthened the supportive leadership–engagement link (β = 0.150, p < .001), but did not moderate the engagement–well-being association (β = 0.063, p = .152). Findings suggest that leadership support and affective–motivational engagement are central levers for workforce well-being in SMEs, while digital health competence enhances employees’ responsiveness to supportive leaders.